Scopoletin potentiates the anti-cancer effects of cisplatin against cholangiocarcinoma cell lines - Asgar, Md. Ali; Senawong, Gulsiri; Sripa, Banchob; Senawong, Thanaset (Bangladesh Journal of Pharmacology, 2015)
Chemotherapy with cisplatin in cholangiocarcinoma produces adverse effects and leads to resistance development by tumors. We aimed to evaluate anti-cancer effects by co-administration of cisplatin and scopoletin in cholangiocarcinoma cells. MTT assay, median effect principle, cell cycle arrest and apoptosis assay were conducted to determine anti-cancer effects. Results revealed that treatment with cisplatin and scopoletin resulted in dose-dependent reduction of cell viability for cholangiocarcinoma cells. Combination of these agents inhibited proliferation of cells significantly more than single agent either. Combination indices reflect additive cytotoxic effect, leading to >2 times dose reduction for each agent. Both the cell cycle arrest (G0/G1) and apoptosis induction underling the enhanced cytotoxicity for the combination. Besides, single agent conferred cell cycle arresting and apoptotic effects in cholangiocarcinoma cells. By contrast, non-cancer cells were less affected with combination. Our observations suggest that cisplatin and scopoletin combination may bring positive significance in cholangiocarcinoma treatment.